Advances in computers., volume 57 Information repositories - Zelkowitz, Marvin V., 1945- (San Diego, Calif. ; London : Academic, 2003)
Advances in Computers remains at the forefront in presenting the new developments in the ever-changing field of information technology. Since 1960, Advances in Computers has chronicled the constantly shifting theories and methods of this technology that greatly shape our lives today. Information Repositories focuses on the use of large data repositories to store and retrieve information. This series is an invaluable addition to any university course in computer technology, as well as finding itself at home on the bookshelf of industrial practitioners. * Includes in-depth surveys and tutorials on advances in Computer Technology. * Features the work of well-known authors and researchers in the field. * Provides a broad overview of important developments. * Contains extensive bibliographies.
Preface. -- Contributors. -- On the nature and importance of archiving in the digital age, H.R. Tibbo. -- Preserving digital records and the life cycle of information, S. Chen. -- Managing historical XML data, S.S. Chawathe. -- Adding compression to next-generation text retrieval systems, N. Ziviani, and E. Silva de Moura. -- Are scripting languages any good? A validation of Perl, Python, Rexx, and Tcl against C, C++, and Java, L. Prechelt. -- Issues and approaches for developing lerner-centered technology, C. Quintana, J. Krajcik, and E. Soloway. -- Personalizing interactions with information systems, S. Perugini, and N. Ramakrishnan.
Διαθέσιμο και σε ηλεκτρονικό βιβλίο, τρόπος πρόσβασης μέσω διαδικτύου.
Keywords: Computer science -- Periodicals; Electronic data processing -- Periodicals; Electronic books